"O Concreto já rachou" : o movimento punk de Brasília como herdeiro da MPB - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
With the research “O concreto já rachou”: the Punk movement of Brasília as an heir of MPB, we intend to understand the representative and historical impacts of the period of the Brazilian military dictatorship (1964-1985) on musical movements, in this case MPB and Punk. The decree of the censorship by the institutional act number 5 in 1968 and the advance of the cultural market delimited the course of the artistic productions in the country, as well as the wave of public demonstrations that marked the world divided by the then Cold War. The generations of the 60s and 70s became marked by the political engagement, by the hedonism in counterpoint to the social transformations and by the denial of values, attributes of youth that advocated the production of music as social chronicles. With the rise of the cultural industry, the MPB has become one of the main genres of song engaged and critical in times of authoritarianism and censorship departments, in which artistic creativity has raised means of cheating. In the 80s, rock presents itself as the new trigger of the music industry, although this new generation of a decadent regime and the process of re-democratization to be already present, it carries the same precepts of the protest of the musicians of the previous decades, but less willing to embrace utopian ideas. The Punk movement of Brasília denotes the perspective of a more brutal youth that demystifies the founding myths of the modernist symbol city, while they are figures close to the center of the political power. Yet, however much the aspirations of all these generations were based on social changes, both MPB and Punk reconfigured themselves presenting a more commercial and individualistic logic, while the music of the new generation of the end of the twentieth century moves towards apolitical romanticism.
Keywords: Punk; MPB - História - Ditadura.; Ditadura - Indústria cultural; Punk; MPB - History - Dictatorship; Dictatorship - Cultural industry; Cultural industry; CIENCIAS HUMANAS::HISTORIA; CIENCIAS HUMANAS::CIENCIA POLITICA